Inglorious Passages. - Wills, Brian Steel (Modern war studies., 2017)
The first book to chronicle the degree to which noncombat deaths impacted the men and women who offered their services and gave their lives in the factories and fields of the Union and the Confederacy from 1861 to 1865.